2015
DOI: 10.1007/s13105-015-0418-8
|View full text |Cite
|
Sign up to set email alerts
|

S-resistin, a non secretable resistin isoform, impairs the insulin signalling pathway in 3T3-L1 adipocytes

Abstract: S-resistin is a non-secretable resistin spliced variant, which is expressed mainly in the white adipose tissue from Wistar rats. Previous results confirmed that 3T3-L1 cells expressing s-resistin (3T3-L1-s-res) showed an inflammatory response and exhibited a decrease in glucose transport, both basal and insulin-stimulated. Here we present evidences demonstrating for the first time that s-resistin, like resistin, blocks insulin signalling pathway by inhibiting insulin receptor, insulin receptor substrate 1, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Other cytokines secreted from the adipose tissue and by cells participating in inflammatory processes (e.g., macrophages or neutrophils) is resistin (28, 29). Many studies have described its role in inflammatory processes including CTDs such as rheumatoid arthritis (8, 9, 30) or SLE (7).…”
Section: Discussionmentioning
confidence: 99%
“…Other cytokines secreted from the adipose tissue and by cells participating in inflammatory processes (e.g., macrophages or neutrophils) is resistin (28, 29). Many studies have described its role in inflammatory processes including CTDs such as rheumatoid arthritis (8, 9, 30) or SLE (7).…”
Section: Discussionmentioning
confidence: 99%
“…To date, our knowledge about the biological function of s-resistin comes from in vitro studies performed in 3T3-L1 cells expressing both s-resistin and resistin sequences. These results showed that s-resistin, like resistin, impaired insulin action in adipocytes 21 and inhibits adipocyte differentiation by stimulation of the expression of pro-inflammatory molecules, such as TNF-α and interleukin 6 (IL-6) 22 . Interestingly, s-resistin significantly increased the expression and secretion of TNF-α at early stages of adipocyte differentiation 22 .…”
Section: Introductionmentioning
confidence: 98%